EFEKTIFITAS OPERSIONAL PENGAWASAN PENDIRIAN BANGUNAN OLEH DINAS TATA RUANG DAN BANGUNAN KOTA PEKANBARU - Dea Ardhianta; Ernawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Phenomena of this research is the development effectiveness in Pekanbaru city that is still much to do in the town center. Her reality is still a lot of development is done only in the city center so no way RTRW pekanbaru city. Whereas in the RTRW cities pekanbaru mention that the focus in the area of development in the periphery.The purpose of this study was to examine the effectiveness of operational supervision of construction of the building by the department of spatial planning and building the city of Pekanbaru. Where to see the development that is still flourishing in the city center when RTRW city pekanbaru pekanbaru mentioned that the construction will be focused into a suburb. From the results of this study found factors that affect surveillance that changes always occur both from outside and from within the organization, organizational complexity requires formal supervision because of the decentralization of power and errors / irregularities committed member organizations require supervision.This research was conducted in the city of Pekanbaru, the Department of Spatial and Building Pekanbaru City where the sample is head and staff department spatial planning and building cities pekanbaru, the sampling technique used purposive sampling, data collection method is used obserfasi, interviews and documentation. Once the data is collected and analyzed using triangulation techniquesHaving done the research found that the effectiveness of supervision of construction in Pekanbaru city is not maximized, it can be seen from Handayaniggrat that in the review of the 5 indicators of direct supervision, indirect supervision, supervision formal, no formal supervision and administrative oversight.Keywords : Effectiveness, Supervision, Supervision Of Direct, Indirect Supervision, Supervision Formal, No Formal Supervision And Administrative Oversight.